On the mean convergence of Fourier–Jacobi series - Goncharov, S. V.; Motornyi, V. P.; Nitiema, P. K. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The convergence of Fourier–Jacobi series in the spaces $L_{p,A,B}$ is studied in the case where the Lebesgue constants are unbounded.